(untitled) (Bangladesh Journal of Psychiatry, 2017)
Diabetes mellitus (DM) is a chronic condition which is associated with long term damage, dysfunction and failure of various organs. Many psychiatric disorders associated with DM have been also reported and among them major depressive disorder (MDD) and generalized anxiety disorder (GAD) are more common. The objective of the study was to find out the proportion of MDD and GAD among the patients with DM. This was a cross sectional study conducted in North Bengal Medical College hospital, Sirajgang, Bangladesh during the period from 1st January 2016 to 30th June 2016. For this purpose, 80 diabetic patients satisfying inclusion and exclusion criteria were selected from primarily selected sample done by convenient sampling technique. Data were collected by face to face interview using semi-structured questionnaire. MDD and GAD were confirmed by Diagnostic and Statistical Manual for Mental Disorders, 5th edition (DSM-5) among the respondents who were found screened positive by General Health Questionnaire-12 (GHQ-12). The results showed that maximum respondents 29 (36.2%) were in the age group between 40-49 years with male predominance (57%). Among the respondents 52 (65%) were married, 48 (60%) came from a lower class family and 46 (57.5%) were rural resident. General Health Questionnaire-12 (GHQ-12) was positive in 35 (43.7%) of respondents. Among them 18 (22.5%) were suffering from MDD and 11 (13.7%) were suffering from GAD. It was shown that both MDD and GAD were higher among female patients. So physicians should pay attention to rule out psychiatric disorders in patients with DM. Bang J Psychiatry June 2015; 29(1): 14-17